Concepções e práticas dos docentes da UFC sobre avaliação do ensino-aprendizagem - Mesquita, Daniela Graciela Silva Brito de (2016)
The practice of evaluation is present in the professional life of every teacher. It is understood that the evaluation should guide the actions of any educator, whereas the evaluation of teaching and learning process lends itself not only to value and assign value and award grades, but also verify what methodology should be better used and whether it is achieving its purpose. Researches in this area are important because they contribute to understand phenomena related to the evaluation of teaching and learning process in different fields of knowledge. Therefore, the main goal of this study is to investigate the conceptions and practices of UFC professors concerning the evaluation of teaching and learning process. The specific objectives are: verify how UFC professors understand conceptions associated with the evaluation of teaching and learning process; compare the point of view of the UFC professors about the evaluation of teaching and learning process, by field of knowledge; identify the pedagogical practices of evaluation, evaluation instruments and teaching modalities of exposition used by UFC professors; and compare trends related to understanding of approaches in the educational process with the pedagogical practices adopted by UFC professors. Therefore, a quantitative survey was conducted with a sample of 129 professors in the field of exact sciences and human sciences, whose universe was composed by the professors from Science Center, Technology Center, Humanities Center and Education College. The research was done through a questionnaire published on google docs, in order to identify the professors’ perception about the evaluation of teaching and learning process. Among other results, the survey reveals that there is a tendency for Exact Sciences to be humanistic in theory and practice, and for Human Sciences to be humanistic and cognitive in theory and practice.